Jak to jest być nietoperzem? Refleksje przy lekturze eseju Thomasa Nagela - Wężowicz-Ziółkowska, Dobrosława (Zoophilologica. Polish Journal of Animal Studies, 2015)
The article asks questions about the human cognitive abilities – how it is to be an animal of a species different from one’s own. Using as a basis the doubts of the philosopher Thomas Nagel, the author proceeds to discuss the standpoint of ethnologists Frans de Waal and Konrad Lorenz, who accept the limitations of the human cognitive apparatus and language, with the help of which we describe what we call the “animal.” The author suggests that the problem of contemporary humanities and animal studies lies not in anthropodenial, but in anthropomorphism, rooted in the centrism typical of our species, which seems impossible to overcome. The author also proposes a thesis that the way to overcome this issue is for people to gain knowledge about these limitations. This knowledge, supported by interspecies empathy, developed in the process of coevolution of animal species (humans being one of them), is the most effective tool of heuristics.